The role of Traditional Property Rights in the sustainable use of Rural Lands in the Techiman Municipality - Anaafo, David (2011)
Thesis submitted to the School of Graduate Studies Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfillment of the requirements for the Master of Science Degree (M.Sc.) in Development Planning and Management.